Perfection in creation from the perspective of the Quran: The necessity of the creation alterations - Masoud Alebouyeh; Mostafa Esmaeili (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: To meet the growing need for food and drugs to improve quality of life, new technologies (e.g. biotechnology and genetic engineering) have attracted politicians and food producers worldwide. Aberrant application of these technologies could cause irreparable consequences that can be life threatening. Changes of genetic entity for improvement and reconstruction of the creation for usage in modern world are main topic under consideration in these technologies. However, there are many controversies for their application in the world. Method: In this study, by reviewing the Quran, Hadiths, and articles, we tried to provide a discussion on limitations, justifiability or illegality of the creation change. The researchers observed all ethical issues in the study and declared no conflict of interests. Results: The provided data showed that change in the creation occurs naturally in the physical dimension, in contrast to the spiritual view, and seems to be allowable provided by the preserve of the entity of the creation. Conclusion: With respect to the ethical issue and nature of the creatures, manipulation of the creation for the sake of their improvement in function and activity toward normal status seems to be allowable. For downloading the full-text of this article please click here. Please cite this article as: Alebouyeh M, Esmaeili M. Perfection in creation from the perspective of the Quran: The necessity of the creation alterations. J Res Relig Health. 2019; 4(5):118- 128.